Mental Fatigue and Adversity Quotient: A Correlational Analysis of Final Year Students Working on Thesis - Thalib, Tarmizi; Zhohiru, Muhammad; Gismin, Sitti Syawaliyah (Universitas Muhammadiyah Surakarta, 2024)
This research aims to see whether there is a relationship between mental fatigue and the adversity quotient in college students working on their thesis. This type of research is a survey that aims to see the relationship between mental fatigue and the adversity quotient in final students working on their thesis. The sampling methed used incidental sampling. The research sample was 105 final students who were writing their thesis from different faculties. This instrument uses two models, namely mental fatigue with the